Weight loss methods and effects on the different combat sports athletes - Çolak, Adem; Sahin, İbrahim and Soylu, Yusuf and Koç, Mine and Öcal, Tuncay (Progress in Nutrition, 2020)
Study Objectives: This study was carried out to determine the weight reduction methods of athletes engaged in weight sports. The sample of the study consists of 99 judo players, 89 taekwondo players, 74 wrestlers and 262 athletes in Ankara. Methods: In this study, athlete weight reduction methods and effects scale was developed by Yarar et al. (2016) and personal information form developed by the researcher were used as data collection tools. Independent sample test and one-way ANOVA were used for percentage, frequency, arithmetic distributions, and Tukey HSD and Spearman Correlation test, which are the second level tests, were used for significant differences between ANOVA analyzes. Results: As a result, judo, taekwondo and the wrestling athletes were slightly affected by the diet size. There was a difference in weight reduction behaviors according to gender. Again, male athletes were more affected by fluid loss than girls. Significant differences were found in case of physiological, Psychological and fluid loss sub-dimensions. It was determined that wrestlers used Psychological methods. According to the age variable of the athletes, the sub-dimensions are mostly used by athletes aged 19 and over. Conclusion: It is a point that regularly athletes’ bodyweight must be controlled to prevent their loss of weight in pre-competitive. Such an approach is beneficial for both athletes’ health and performance. In cases where adult athletes must lose weight, it would yield better results to determine the percentage of body fat and to lose weight by reducing the rate of fat.